Identification of BmSP25 gene in Bombyx mori with antiviral function against BmNPV - Yonghong Zhang; Yajin Li; Zhengqin Wang; Jiafu Luo; Lingli Li; Hongrui Zhang (PLoS ONE, 2026)
Bombyx mori serine protease (BmSP) is constitute a gene family of proteolytic enzymes characterized by serine residues at their active sites and play critical roles in physiological processes, including digestion, growth and development, and immune responses. As a member of the BmSP family, BmSP25 exhibits differential expression following Bombyx mori nucleopolyhedrovirus ( BmNPV ) infection. Our result demonstrated that BmNPV infection upregulated BmSP25 expression in both resistant (SuN) and susceptible (P50) silkworm strains, with a more pronounced response observed in SuN than in P50. To further investigate its function, siRNA-mediated knockdown of BmSP25 in BmN cells promoted the proliferation of recombinant BV-EGFP virus, whereas overexpression of BmSP25 significantly suppressed BmNPV replication. To validate its antiviral activity at the organismal level, transgenic silkworm strains overexpressing BmSP25 ( BmSP25 -OE) and BmSP25 knockout strains ( BmSP25 -KO) were generated. Following oral inoculation with BmNPV , viral proliferation was significantly inhibited in the BmSP25 -OE strain, whereas viral replication was notably enhanced in the BmSP25 -KO strain. This study is the first to clearly demonstrate the anti- BmNPV function of BmSP25 in silkworms, providing a foundation for further elucidation of its role in host immune defense mechanisms and identifying a potential genetic target for molecular breeding aimed at improving disease resistance in silkworms.